Climate, buildings and occupant expectations: a comfort-based model for the design and operation of office buildings in hot humid conditions - Kishnani, Nirmal (Curtin University, 2002)
Office buildings in hot humid Singapore appear to be designed for stable and uniform indoor conditions. It is proposed in this thesis that this is unnecessary, as occupant comfort expectations do not warrant it and energy is wasted as a result. A comfort-based approach to design is advocated, as a means of balancing user needs with the objective of energy conservation.This issue of how perception of comfort is linked with indoor stability emerged from the question, 'why do office buildings, despite Bioclimatic prescriptions for hot humid conditions, continue to be predominantly climate rejecting and active-run?' The literature was found to be polarised by arguments for architectural solutions that are climatically responsive and present lower energy costs, and those for engineered solutions that deliver greater, more consistent comfort, albeit through reliance on electro-mechanical systems.It is argued that comprehending the gaps in the literature, and between theory and application, requires a better understanding of occupant comfort. This would be an inside-out view of comfort and climate, predicated on how the occupant is affected by the building and the cognitive nature of comfort itself.Relying on a sample of office buildings, the thesis set out to establish the following:Prevalence of the climate-based approach, specifically Yeang's Bioclimatic ModelPrevalence of uniformity and stability of the indoor environmentOccupant perception of indoor comfort, both thermal and visual, particularly with regard to variability of ambient conditionsOccupant perception of various operational modes: passive, mixed and activeThese goals were addressed through observations of form, envelope and layout, occupant surveys and the monitoring of buildings in passive and active modes.It was found that the Bioclimatic approach is non-existent in the context of the Singapore office building. In the case of two Bioclimatic buildings in Malaysia, the Model is not consistently applied. This disparity appears partly due to conflicting priorities, in particular style, cost and client pressures, and partly due to assumptions about occupant comfort.The Singapore office building was found to be predominantly active-run, operating within a narrow bandwidth of temperatures across most spaces. Occupant perception of variability outside the primary workplace, however, is one of acceptance, even preference. It was found through analysis of user feedback that the office building, on the basis of comfort expectations, could be divided into three activity zones: Work, Support and Transit.This 3-tiered structure was subsequently tested through a large-scale, longitudinal survey carried out across three spaces, each representing an activity zone, within a single building. The survey was accompanied by adjustments to the building's temperature settings to test the limits of acceptance in each zone. Findings from this exercise support the notion of a three-zoned office building, in which thermal conditions for each zone could be varied without affecting comfort. Energy figures that were monitored before and after the resetting showed drops of 7.1 % in chiller consumption and 2.9% in overall consumption.These findings led to a comfort-based, tri-modal proposal for office buildings in hot humid conditions, defined as the Psychoclimatic Model for its basis in comfort expectations and the interaction between climate, building and the occupant.The implications of the thesis outcome on regulatory control in Singapore and thermal comfort theory are discussed. Recommendations are made for future research into other building types and national context, plus a parametric study into the full energy-saving potential of the Psychoclimatic Model.